2022
DOI: 10.3389/fnut.2022.833730
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Nutritional Components and Phytochemical Attributes of Selected Thai Rice Bran

Abstract: It is important to raise awareness regarding rice's nutritional quality and health benefits in terms of enhancing rice consumption in people's daily diets. This study evaluated the proximate components and phytochemical profiles of 11 Thai rice bran varieties, 4 non-colored rice brans and 7 colored rice brans, collected from the same agricultural fields. The chemical composition (ash, fat, proteins, fiber, and gross energy) was determined using proximate analysis methods. High-performance liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…PCA is a useful statistical tool for identifying variations between samples and visualizing the cluster of samples depending on variation [ 41 , 42 ]. In this study, PCA was used to classify black rice varieties according to their phytochemical components, antioxidant and anti-inflammatory properties to finally categorized the black rice varieties into three groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCA is a useful statistical tool for identifying variations between samples and visualizing the cluster of samples depending on variation [ 41 , 42 ]. In this study, PCA was used to classify black rice varieties according to their phytochemical components, antioxidant and anti-inflammatory properties to finally categorized the black rice varieties into three groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to the PCA results, a high levels of phytochemicals, total phenolics, flavonoids, anthocyanins, and C3G contents, along with high antioxidant properties were categorized into group A. A previous study reported that KAK 1, PES 1, SNG 5 and BKU 5 possessed high protein contents, crude fiber, and mineral contents [ 42 ]. Our findings provide evidence that the black rice varieties, KAK 1, PES 1, SNG 5 and BKU 5, might be the appropriate choices for the consumers who looking for the functional food with high antioxidant as well as high protein and fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the procedure of Arjin et al [ 66 ], the samples were dissolved in 0.01% formic acid and ethanol (1:1, v/v ) to achieve a final concentration of 1 mg/mL, and then purified with the QuEChERS dispersive SPE kit, fat + pigments (Agilent Technology, Santa Clara, CA, USA) prior to being filtered through a 0.22 µm membrane. The phenolic compounds of extract were quantified and analyzed in liquid chromatography (Agilent 1260 Infinity II series), equipped with an electrospray ion quadrupole mass spectrometer 6130 (Agilent Tech., Santa Clara, CA, USA), according to the reported method [ 39 , 67 ]. Solvent A was 5% formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…VCO contains 92% of saturated fatty acids (in the form of triglycerides) and most of them (about 62–70%) are medium-chain fatty acids [ 20 ]. RBO contains approximately 80–85% unsaturated fatty acids [ 21 ], whereas PO comprises approximately equal amounts of saturated and unsaturated fatty acids [ 22 ]. The difference in compositions of these vegetable oils may possess different physicochemical properties and benefits.…”
Section: Introductionmentioning
confidence: 99%